The Effect of Different Kinds of Self-Talk on Balance Function of the Healthy Elderly - Amir Shariati; Jamal Fazel Kalkhoran (University of Tehran, 2013)
The aim of the present study was to investigate and compare the effects of twokinds of motivational and instructional self-talk on the performance of static anddynamic balance tasks in the elderly. For this purpose, 45 old subjects agedbetween 60 and 70 from Qom province participated in this study. Static balancetask (stand on one leg) and dynamic balance task (SEBT test) were instructed withno self-talk intervention. Then, they were divided into three groups: motivationalself-talk, instructional self-talk and control. One-way analysis of variance andTukey post hoc test were used to analyze the data. The results showed a significantdifference among the groups. The result of Tukey post hoc test showed nosignificant difference in static balance task between instructional and motivationalself-talk (P>0.05). Also, in dynamic balance task, instructional self-talksignificantly improved balance function compared to motivational self-talk(P<0.05). Generally, self-talk as a cognitive strategy was effective in performingbalance tasks and motivational self-talk was preferred in dynamic balance tasks.